Improved Purification of Human Granzyme A/B and Granulysin Using a Mammalian Expression System - Rasi, Valerio; Hameed, Owais Abdul; Matthey, Patricia; Bera, Sibes; Grandgenett, Duane P.; Salentinig, Stefan; Walch, Michael; Hoft, Daniel F. (Frontiers in Immunology, 2022)
Cytotoxic lymphocytes release proteins contained within the cytoplasmic cytolytic granules after recognition of infected or tumor target cells. These cytotoxic granular proteins (namely granzymes, granulysin, and perforin) are key immunological mediators within human cellular immunity. The availability of highly purified cytotoxic proteins has been fundamental for understanding their function in immunity and mechanistic involvement in sepsis and autoimmunity. Methods for recovery of native cytotoxic proteins can be problematic leading to: 1) the co-purification of additional proteins, confounding interpretation of function, and 2) low yields of highly purified proteins. Recombinant protein expression of individual cytolytic components can overcome these challenges. The use of mammalian expression systems is preferred for optimal post-translational modifications and avoidance of endotoxin contamination. Some of these proteins have been proposed for host directed human therapies (e.g. - granzyme A), or treatment of systemic infections or tumors as in granulysin. We report here a novel expression system using HEK293T cells for cost-effective purification of high yields of human granzymes (granzyme A and granzyme B) and granulysin with enhanced biological activity than previous reports. The resulting proteins are free of native contaminants, fold correctly, and remain enzymatically active. Importantly, these improvements have also led to the first purification of biologically active recombinant human granulysin in high yields from a mammalian system. This method can be used as a template for purification of many other secreted cellular proteins and may lead to advances for human medicine.